2020
DOI: 10.1002/ese3.774
|View full text |Cite
|
Sign up to set email alerts
|

Self‐powered light‐induced plating for III‐V/Ge triple‐junction solar cell metallization

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…After epitaxy, one of the major costs during the fabrication of III-V solar cells is the front contact metallization [2]. Several variations of the metallization and/or metal deposition technique have been studied in order to reduce this cost [6][7][8][9]. In particular, it was shown that the standard AuGe/Ni/Au front ohmic contact metallization could be replaced by a thin Pd/Ge/Ti/Pd stack combined with a thick Al layer [9].…”
Section: Introductionmentioning
confidence: 99%
“…After epitaxy, one of the major costs during the fabrication of III-V solar cells is the front contact metallization [2]. Several variations of the metallization and/or metal deposition technique have been studied in order to reduce this cost [6][7][8][9]. In particular, it was shown that the standard AuGe/Ni/Au front ohmic contact metallization could be replaced by a thin Pd/Ge/Ti/Pd stack combined with a thick Al layer [9].…”
Section: Introductionmentioning
confidence: 99%